Beobachtungen zur klima-morphologischen Höhenstufung der Cordillera Real (Bolivien) - Hastenrath, Stefan (ERDKUNDE, 1971)
Field observations taken during travel through the Cordillera Real in June 1969 are evaluated in conjunction with meteorological data and air photographs. The temperature field in the free atmosphere over the Altiplano and the Cordillera Real is examined on the basis of radio-sonde ascents and surface measurements. Turf exfoliations occur from about 4,400 m upward, which is somewhat above the 0°C level of mean minimum temperature. A belt of bound solifluction with turf garlands, etc., extends from here to about 5,000 m, where the grass cover terminates abruptly. This is considered the lower limit of the belt of free solifluction, comprising stone stripes, stone nets, polygon soils, and stone packings. Its upper limit is given by the snow line in about 5,400 m. Penitentes are a characteristic form of ablation here.